Measuring anxiety related to COVID-19: A Turkish validation study of the Coronavirus Anxiety Scale. Issue 5 (28th May 2022) - Evren, Cuneyt; Evren, Bilge; Dalbudak, Ercan; Topcu, Merve; Kutlu, Nilay
Abstract: The aim of the current study is to validate the Turkish version of the Coronavirus Anxiety Scale (CAS). Participants were assessed across the CAS, Obsession with COVID-19 Scale (OCS) and Fear of COVID-19 Scale. We surveyed 1023 Turkish native speakers who participated online. Confirmatory factor analysis showed that the factor structure of the CAS was satisfactory. The scale was internally consistent with a Cronbach's alpha of 0.80. Positive correlations of the CAS with the OCS and the Fear of COVID-19 Scale demonstrated adequate convergent validity. These findings suggest that the CAS is a valid and reliable measure to assess the severity of dysfunctional coronavirus related anxiety.